THE ANTIMALARIAL AND TOXICITY STUDIES OF SWAZI MEDICINAL PLANTS - Sibandze, G. F.; van Zyl, R. L. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Malaria, caused by Plasmodium falciparum, is a major cause of morbidity and mortality in sub- Saharan Africa. Many of the standard antimalarial drugs have become ineffective due to the parasite developing resistance against them. Traditional medicine is a source of primary healthcare in most societies in Africa, with about 80 % of the people consulting traditional medical practitioners for healthcare. Traditional healers use various medicinal plants to treat malaria according to its “flu-like” symptoms and fever. In consultation with Swazi traditional healers, fifteen Swazi plants were selected and screened for their antimalarial activity and toxicity profiles. The plants were collected from the Manzini region in Swaziland, air-dried and extracted with dichloromethane: methanol (1:1). Antimalarial activity against P. falciparum was determined using the tritiated hypoxanthine incorporation assay. Toxicity profiles of the extracts were tested on human red blood cells and kidney epithelial cells. Of the 33 extracts tested, 5 displayed in vitro antimalarial activity with IC50 values less than 20 Âµg/ml, namely Terminalia phanerophlebia (leaves), Berkheya setifera (stem/root), Priva meyeri (whole plant), Trichilia emetica (leaves) and Breonadia salicina (bark). The five most active extracts did not cause red blood cell haemolysis at concentrations ten times greater than the IC50. Similarly, T. phanerophlebia, B. setifera and B. salicina were not toxic to the kidney epithelial cells. However, P. meyeri and T. emetica displayed toxicity (IC50 = 14.633 Â± 1.616; 45.945 Â± 5.104 Âµg/ml), respectively. The study supports the traditional use of some of the plants in the treatment of the “flu-like” and fever symptoms of malaria